KOMUNIKASI DAKWAH KUA DAN HARMONISASI UMAT DI KECAMATAN SANDUBAYA - Achmad Syahril Hamdani; Wisri (Fakultas Dakwah Universitas Ibrahimy, 2026)
This study aims to analyze and describe the communication strategies applied by the Sandubaya Subdistrict Religious Affairs Office (KUA) in promoting religious moderation to create harmony among religious communities in the region. This study uses a qualitative approach with a case study design. Data were collected through participatory observation, indepth interviews with KUA officials and community leaders, and documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing to ensure the validity of the findings. The results showed that the Sandubaya Subdistrict KUA's da'wah communication was carried out through the integration of two main approaches: da'wah billisan (verbal communication) and da'wah bil-hal (concrete actions). This strategy is implemented through three pillars of activity, namely: 1) Massive socialization in the “Kampung Moderasi Beragama” (Religious Moderation Village), 2) Institutionalization of moderate values in the social structure, and 3) Integration of inclusive creed material. This approach has proven effective in minimizing extreme understandings and strengthening tolerance in a pluralistic society. This study emphasizes the role of the KUA not only as an administrative unit for marriage, but also as a strategic facilitator in da'wah communication based on strengthening religious moderation at the grassroots level.